Supply-Use and Input-Output Tables - Sourish Dutta (Cambridge University Press, 2022)
The Supply-Use Tables (SUTs) form a central part of the national accounts, providing a framework to bring together a range of data and, through balancing, to ensure the coherency and consistency of various parts of the national accounts. The SUTs thus serve many purposes, in particular, statistical and analytical, not just for producers but also for a range of different users, and their analytical dimension is especially enhanced when the SUTs are transformed into Input-Output Tables (IOTs). For analytical purposes, the assumptions about the relationships between inputs and outputs are required irrespective of whether the products have been produced by the primary industry or by other industries as their secondary output.
Keywords: 330; Supply-Use Tables; Input-output Tables